MKT J170456.2–482100: the first transient discovered by MeerKAT. Issue 1 (30th October 2019) - Driessen, L N; McDonald, I; Buckley, D A H; Caleb, M; Kotze, E J; Potter, S B; Rajwade, K M; Rowlinson, A; Stappers, B W; Tremou, E; Woudt, P A; Fender, R P; et al.
ABSTRACT: We report the discovery of the first transient with MeerKAT, MKT J170456.2–482100, discovered in ThunderKAT images of the low-mass X-ray binary GX339–4. MKT J170456.2–482100 is variable in the radio, reaching a maximum flux density of 0.71± 0.11 mJy on 2019 October 12, and is undetected in 15 out of 48 ThunderKAT epochs. MKT J170456.2–482100 is coincident with the chromospherically active K-type sub-giant TYC 8332-2529-1, and 18 yr of archival optical photometry of the star shows that it varies with a period of 21.25± 0.04 d . The shape and phase of the optical light curve changes over time, and we detect both X-ray and UV emission at the position of MKT J170456.2–482100, which may indicate that TYC 8332-2529-1 has large star spots. Spectroscopic analysis shows that TYC 8332-2529-1 is in a binary, and has a line-of-sight radial velocity amplitude of 43 km s^-1 . We also observe a spectral feature in antiphase with the K-type sub-giant, with a line-of-sight radial velocity amplitude of 12± 10 km s^-1, whose origins cannot currently be explained. Further observations and investigation are required to determine the nature of the MKT J170456.2–482100 system.